A Dynamic Hajj Fiqh for Elderly: A Study of Indonesian Pilgrims - Badrah Uyuni; Mohammad Adnan (International Journal of Emerging Issues in Islamic Studies, 2024)
Hajj, one of the pillars of Islam, requires physical and mental capability, making it more suitable for healthy individuals. Recognizing the strong desire of older Muslims to perform Hajj, several countries have implemented "Elderly Friendly Hajj" programs. These initiatives aim to ensure senior citizens can participate in Hajj with greater comfort, reflecting Islam's inclusive values and ease of worship. This research investigates the 2023 Elderly Friendly Hajj Program to provide an evaluation for the Indonesian government to enhance the following year's Hajj organization. The study employs a narrative literature review model, comparing data on Hajj and Fiqh for senior citizens, observations of pilgrims, and literature on Hajj policies and regulations. Additionally, interviews with Hajj officers and pilgrims were conducted to gather firsthand insights. The data was analyzed using descriptive analysis. The findings reveal that the government is continuously improving the Hajj system and management, focusing on prioritizing elderly pilgrims. Significant emphasis is placed on providing senior citizens maximum comfort and worship opportunities through enhanced infrastructure, tailored services, and adjustments in Fiqh laws to accommodate their needs. This study underscores the importance of inclusive practices in religious observances, ensuring senior citizens can fulfil their spiritual obligations with dignity and ease. The evaluation aims to assist the Indonesian government in making informed decisions to improve Hajj services for the elderly further in the future.